The Effect of Fermentation Using Lactobacillus acidophilus on Conjugated Linoleic Acid in Goat Milk - Indratiningsih, Indratiningsih (2012)
Milk and milk product are nutritious food items containing numerous essential nutrients. The content of conjugated linoleic acid may promote positive health effects. Fermented dairy foods have long been considered safe and nutritious. Animal foods are rich in CLA (Conjugated Linoleic Acids) and dairy products are the major sources of CLA. The objective of this study was to investigate to increase CLA in goat milk through fermentation process using bacteria L. acidophilus (La) that produced acidhopilus milk. Goat milk was fermented with different level of L.acidophilus (1.0, 3.0 and 5.0%) and incubated at 37 0 C for 5 hours. The result indicated that fermentation processing increased CLA. There was significant different of CLA concentration between fresh milk and fermented milk (p<0.05), CLA was 0.89 – 0.99 % of total fatty acids, but no significant difference between fermented milk.As conclusion, fermentation with L,acidophilus increased CLA concentration.